Prediction and explanation of the aeroelastic behavior of a square-section cylinder via forced vibration. Issue 176 (May 2018) - Ma, C.M.; Liu, Y.Z.; Li, Q.S.; Liao, H.L.
Abstract: The work presented in this study concerns the existing link between fluctuating transverse force characteristics and aeroelastic instability phenomena, which is a step toward further understanding the complex nature of the interactions between square cylinders and air flow. First, by using experimental data from forced vibration, a predictive calculation of the free vibration of an elastically mounted cylinder is carried out. It is found that the prediction results appeared to be qualitatively in agreement with the experimental measurements. This agreement indicates that the measurements using the forced vibration technique is a valuable tool for analysis of free vibration behavior of an elastically mounted cylinder, particularly in cases where the quasi-steady theory is not entirely valid. Furthermore, a new and simple insight into the link between the unsteady force characteristics and the free vibration amplitudes is proposed in this study. Although this approach does not offer details about the nature of the separated flow field around the cross-sections of cylinders, certain complex free-vibration behaviors of square cylinders can be easily interpreted from this perspective. Highlights: A free-vibration prediction method based on forced-vibration technique is proposed. Some typical VIV-galloping interaction and separation phenomena can be successfully reappeared. A new and intuitive insight into the link between fluctuating force characteristics and free-vibration amplitudes is proposed. Certain complex aeroelastic behaviors can be easily interpreted from the new perspective.